2020 14th European Conference on Antennas and Propagation (EuCAP) 2020
DOI: 10.23919/eucap48036.2020.9135688
|View full text |Cite
|
Sign up to set email alerts
|

RSS-Based DoA Estimation Using ESPAR Antenna for V2X Applications in 802.11p Frequency Band

Abstract: In this paper, we have proposed direction-ofarrival (DoA) estimation of incoming signals for V2X applications in 802.11p frequency band, based on recording of received signal strength (RSS) at electronically steerable parasitic array radiator (ESPAR) antenna's output port. The motivation of the work was to prove that ESPAR antenna used to increase connectivity and security in V2X communication can be also used for DoA estimation. The numerical simulation results show that for every proposed radiation pattern w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…From the table, it can be noted that the antennas manufactured with ITO [22][23][24] do not report a fair agreement between the simulated and measured values of the reflection coefficient throughout the entire frequency range of the study, whereas in this work we can see a reasonable concordance between simulated and measured values. The frequency shift may be due to the manufacturing process and the variations in the permittivity of the substrate.…”
Section: Resultsmentioning
confidence: 50%
“…From the table, it can be noted that the antennas manufactured with ITO [22][23][24] do not report a fair agreement between the simulated and measured values of the reflection coefficient throughout the entire frequency range of the study, whereas in this work we can see a reasonable concordance between simulated and measured values. The frequency shift may be due to the manufacturing process and the variations in the permittivity of the substrate.…”
Section: Resultsmentioning
confidence: 50%
“…However, it has been shown that PPCC-MCP algorithm accuracy is sensitive to correct placement of calibration planes positions [24], while obtained results depend on testing setup [28] parameters, especially the choice of testing directions in horizontal and vertical planes as well as SNR values set for testing signals [24,28]. Moreover, the existing PPCC formulation was created to provide DoA results based on a number of directional radiation patterns, while new ESPAR antennas can have a number of possible radiation patterns that can be used in DoA estimation [32,33] having different performance, especially when testing signals may come from multiple horizontal and vertical directions. Therefore, to be used for DoA estimation together with new ESPAR antennas, including the two-row ESPAR antenna proposed in [31], PPCC-MCP algorithm and associated DoA testing methods have to be generalized.…”
Section: Rss-based Doa Estimation For Two-row Espar Antennamentioning
confidence: 99%
“…Combined connectivity and DoA estimation capabilities can highly improve IoT systems involving WSN nodes and gateways installed on the ground in smart factories, buildings and cities [1][2][3]5,6,25,26]. Moreover, it can be used in modern IoT applications involving long-range communication to such objects as unmanned aerial vehicles (UAVs), high-altitude pseudo-satellites (HAPS) or satellite platforms [29,30,32,33], in which the elevation between transceiver and receiver may change in a fast manner. In this regard particularly interesting and growing application area, in which beamforming plays significant role, is providing multiple access and increased security in satellite and aerial integrated networks for IoT communication [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed antenna, shown in Fig. 1 and described in detail in [11], consists of a single active monopole fed by an SMA connector surrounded by twelve parasitic elements. The ground plane for radiating and passive elements and the layout for switching circuits are on the opposite layers of an inexpensive 1.55 mm thick FR4 substrate.…”
Section: Espar Antenna For V2x Applications In 80211p Frequency mentioning
confidence: 99%
“…Due to this fact, a number of reconfigurable antenna designs were proposed [8]. It was proven that ESPAR antenna can be successfully adopted in V2X communication along with power pattern cross-correlation (PPCC) algorithm to obtain angle of arrival signal with precision under 7°for multiple radiation pattern shapes, even with configurations that exhibit high halfpower beamwidth (HPBW) [9]. This gives the possibility not only to obtain acceptable angle estimation results but also for specific radiation patterns to maintain similar link quality between communicating objects in each direction.…”
Section: Introductionmentioning
confidence: 99%